Terrorism, Religious Intolerance and Ethnic Conflict Issues in the National Education Policy (NEP)-2010 of Bangladesh: An Exploratory Study - Sumon, Nur Muhammud Sajjadul Hoque (Journal of Education and Research, 2015)
Education is considered an instrument to combat the problems of terrorism, religious antagonism and ethnic intolerance. Bangladesh has been experiencing its share of these problems along with other South Asian countries. The recent adoption of the National Education Policy (NEP) of 2010 has been an opportunity to consider how the education system can help address these problems. However, a lack of consensus about interpretations of the issues of terrorism, ethnicity and intolerance among the major political parties and different religious groups has stymied this effort.NEP-2010 may be seen as a victim of politico-religious disagreements among stakeholders, especially due to a strong position from a part of the Islamic community. The three issues are interrelated in the sense that, firstly, they emerge from a lack of respect for diversity, and secondly, the problems arise as much from ideological views, as from social and economic conditions. By considering these realities, this paper will examine how the problems have been recognized and attempted to counter in NEP. Empirical data on people’s perception on NEP and the three issues have been used to buttress the arguments.